1994
DOI: 10.1111/j.1813-6982.1994.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Control and Interest Rates During the Post‐De Kock Commission Period

Abstract: 1) THE CURRENT monetary control mechanism in South Africa, which was implemented on the recommendations of the De Kock Commission (RSA, 1985), is one regulating the cost, rather than the availability of funds at the discount window. As some of the changes associated with the new mechanism were introduced during the early 1980s, and seeing that they were fully in line with the findings of the Commission in 1985, it can be argued that the current period in monetary control started with the appointment of Dr De K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…A managed float for the exchange rate was introduced in 1979, though exchange controls for residents remained. The exchange rate was unified in February 1983 (De Kock Commission 1985, Terence Moll 1992, Nel 1994). Owing to South Africa's increasing political isolation, the experiment failed and the financial rand had to be reintroduced in August 1985.…”
Section: Macroeconomic Management In South Africamentioning
confidence: 99%
“…A managed float for the exchange rate was introduced in 1979, though exchange controls for residents remained. The exchange rate was unified in February 1983 (De Kock Commission 1985, Terence Moll 1992, Nel 1994). Owing to South Africa's increasing political isolation, the experiment failed and the financial rand had to be reintroduced in August 1985.…”
Section: Macroeconomic Management In South Africamentioning
confidence: 99%
“…Empirical studies by Correia and Wormald (1987) and Van Rensburg (1995) have shown the BA to proxy inflation expectations and hence consumer prices, which by definition are a subset of economic events. Further, Nel (1994) observed "… the general course and pattern of the BA rate after 1987 was to a greater degree in harmony with that of the Bank Rate than before this time." As the bank rate is controlled by the Reserve Bank the BA rate could be regarded as a proxy for the official monetary policy of the Reserve Bank.…”
Section: Risk Factors Proxying For Economic Eventsmentioning
confidence: 94%
“…The second De Kock period, 1981 to 1989, saw the intensification of the ever-prevalent racial conflict in South Africa and the subsequent unravelling of the Apartheid regime. The monetary regime changes that took place during this period are well known and substantially investigated in South Africa in a number of papers inter alia by Hodge (2001), Gidlow (1995), De Wet (1986), Goedhuys (1994) and Nel (1994). And although ''the picture presented by our economy in the 1980s was one of doom and decline'' (Goedhuys 1994, 146), the changes introduced by Dr Gerhard de Kock changed the philosophy of monetary policy and conduct to such an extent that the current policy is still based on the principles introduced during the 1980s (Rossouw 2005, 293).…”
Section: S24mentioning
confidence: 99%